Vibração ocupacional em trator 4x2 tda em função da pressão interna dos pneus e da superfície de rolamento - Santos, Viviane Castro dos (2016)
The globalized world appreciates the market competition between big companies, having no difference at all when it comes to the agricultural environment, because in order to acquire more customers, the tractor manufacturers tend to invest in technology to increase the machine’s efficiency. These improvements are required and aim to increase production, reduce production costs and to adapt the machines to their users, in order to have more quality within the work. Several factors can influence the machine operation quality, especially noise, temperature and vibration which may directly affect welfare. The present study aimed to evaluate the whole operator body exposure to vibration as well as his hands and arms on a tractor on the following conditions, three different tire air pressure, two different forward speeds and two different shooting surfaces. The experiment was conducted in the experimental area of the Agricultural Machinery Accident Investigation Laboratory belonging to the Department of Agricultural Engineering of the Federal University of Ceará. The tractor utilized was a 4x2 tractor with auxiliary front wheel drive, Valtra brand, model BM 125i, year 2011 with a power of 91.9 kW (125 HP), maximum speed of 2,300 rotation per minute, equipped with radial tires. The experimental design was a completely randomized factorial 2 x 2 x 3 with two rolling surfaces (uncovered soil and soil covered with (Panicum maximum CV. Mombasa)), two forward speeds (4.3 km. h-1 and 6.4 km h-1), and three different tire air pressure (10, 14 and 18 lbs.pol-2) for the front tires and (12, 16 and 20 lbs.pol-2 ) for the rear tires. The experiment was conducted in accordance with the guidelines determined by the Brazilian operational hygiene standard number 09 and number 10 as well as the international ISO standard 5008, annex A. For the data evaluation, the statistical program ASSISTAT version 7.7 beta was utilized, checked for normality through the symmetry value and kurtosis analysis and consequently subjected to a variance analysis by F test, having the means compared by the Tukey test at 5% significance level. The vibration levels increased due to the increase in speed and the internal air pressure in tires and decreased with the use of the soil covering material. The best working condition was found in the following conditions, operations with soil covering material, at a speed of 4.3 km.h-1, using the tire air pressure at minimum (10 lbs.pol-2 on the front tires and 12 lbs.pol-2 on the rear tires).